Fluorescence lifetime imaging of free and protein-bound NADH. - Lakowicz, J R (1992)
We introduce a methodology, fluorescence lifetime imaging (FLIM), in which the contrast depends on the fluorescence lifetime at each point in a two-dimensional image and not on the local concentration and/or intensity of the fluorophore. We used FLIM to create lifetime images of NADH when free in solution and when bound to malate dehydrogenase. This represents a challenging case for lifetime imaging because the NADH decay times are just 0.4 and 1.0 ns in the free and bound states, respectively. In the present apparatus, lifetime images are created from a series of phase-sensitive images obtained with a gain-modulated image intensifier and recorded with a charge-coupled device (CCD) camera. The intensifier gain is modulated at the light-modulation frequency or a harmonic thereof. A series of stationary phase-sensitive images each obtained with various phase shifts of the gain-modulation signal, is used to determine the phase angle or modulation of the emission at each pixel, which is in essence the lifetime image. We also describe am imaging procedure that allows specific decay times to be suppressed, allowing in this case suppression of the emission from either free or bound NADH. Since the fluorescence lifetimes of probes are known to be sensitive to numerous chemical and physical factors such as pH, oxygen, temperature, cations, polarity, and binding to macromolecules, this method allows imaging of the chemical or property of interest in macroscopic and microscopic samples. The concept of FLIM appears to have numerous potential applications in the biosciences.